EXTREMELY LOUD AND INCREDIBLY CLOSE - Foer, Jonathan Safran, 1977-; Holwill, Helen; Rota, Matt; Pitts, Sorrel (London : PENGUIN BOOKS, 2020)
Penguin Readers is an ELT graded reader series for learners of English as a foreign language. With carefully adapted text, new illustrations and language learning exercises, the print edition also includes instructions to access supporting material online.
Includes questions and excercises
Keywords: Readers; September 11 Terrorist Attacks, 2001 -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Readers